PELAKSANAAN KEBIJAKAN PROTOKOL KESEHATAN BERDASARKAN SURAT KEPUTUSAN BERSAMA (SKB) PADA MASA PANDEMI COVID-19 PADA SEKOLAH DI KOTA PEKANBARU TAHUN 2020 – 2021 - Bahridho Fauzi; Zulfa Harirah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The government has implemented New Normal to restore community activities, especially economic activities while still complying with the Health Protocol. Implementation of learning in the New Normal situation, which is a Joint Decree (SKB) made by 4 Ministers, Minister of Education and Culture, Minister of Religion, Minister of Health, Minister of Home Affairs in responding to the New Normal situation, especially for the implementation of learning. The research objective was to find out about the implementation of the health protocol policy during the Covid-19 pandemic during the Covid-19 pandemic at schools in Pekanbaru City in 2020-2021. Informants from this study were the Pekanbaru City Education Office in the Field of Junior High School Education (SMP), teachers and students in the schools studied. The types of data used in this research are primary data and secondary data. The data collection used in this research was interview and documentation method. The analysis used in this research was descriptive analysis and qualitative analysis. From the research results it is known that the theory used is the concept of Donald S. Van Meter and Carl E. Van Horn theory in Nugroho (2016: 136). The first indicator is the Health Protocol Policy Standards and Targets Based on a Joint Decree (SKB) During the Covid-19 Pandemic at schools in Pekanbaru City based on a Joint Decree (SKB), existing resources are agencies that have the right to oversee the implementation of activities, namely the City Education Office Pekanbaru, all students and teachers in the City of Pekanbaru by communicating this policy to the schools that are their work authority, namely in the City of Pekanbaru. The implementing agents here can be seen the number of teachers and students at the research site, namely Integrated Yabri Middle School, Pekanbaru 44 Public Middle School, Pekanbaru 2 Public Middle School and Pekanbaru 5 Public Middle School. Keywords : health protocol policy, joint decree (skb), during the covid-19 ndemic